2016
DOI: 10.5897/ajb2016.15582
|View full text |Cite
|
Sign up to set email alerts
|

Somatic polyploidization and characterization of induced polyploids of Dioscorea rotundata and Dioscorea cayenensis

Abstract: Genetic improvement of major food yams is constrained by a number of factors, such as the scarcity of flowers and lack of synchronization between male and female flowering. Consequently, somaclonal variation including somatic polyploidization has been considered as a useful tool in yam breeding. Somatic polyploidization and its effect on phenotypic traits of Dioscorea species such as D. alata, D. japonica and D. zingiberensis has been reported; however, optimization of this method in two major yam species, D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Further, polyploid stomatal size can be identified at the cytological level, the polyploid stomatal size also increases with the increase in plant ploidy, and the observation of plant stomatal size can be a further screening for polyploid plants [15]. Liu et al identified the ploidy of Clematis fruticose by observing the stomata and found that tetraploid plants had significantly larger stomata [16].…”
Section: Ploidy Identification Of Begonia × Benariensis Polyploidsmentioning
confidence: 99%
“…Further, polyploid stomatal size can be identified at the cytological level, the polyploid stomatal size also increases with the increase in plant ploidy, and the observation of plant stomatal size can be a further screening for polyploid plants [15]. Liu et al identified the ploidy of Clematis fruticose by observing the stomata and found that tetraploid plants had significantly larger stomata [16].…”
Section: Ploidy Identification Of Begonia × Benariensis Polyploidsmentioning
confidence: 99%